Factors affecting working capital management of small and medium enterprises in Malaysia / Hirnissa Mohd Tahir and Zariyawati Mohd Ashhari. - Mohd Tahir, Hirnissa; Mohd Ashhari, Zariyawati (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Small and medium enterprises (SMEs) in Malaysia are considered as the driving force of the nation's economic growth due to their huge contribution to gross domestic product (GDP). To ensure the contribution sustain, SMEs can maintain their operation with good working capital management (WCM). A positive creation of a firm values can be contributed by a well designed and implemented WCM. The objective of the study is to investigate the factor affecting WCM of SMEs in Malaysia for the period 2010-2013 using panel data analysis. The results indicate that profitability, debt ratio, firm size, and industry types were significantly related to firm's WCM. However, there is lack of evidence to significantly relate sales growth and gross domestic product with firm's WCM.